(untitled) (Samarra Journal of Pure and Applied Science, 2026)
The current study aimed to the synthesis of Nickel Oxide nanoparticles through the use of a biological method (using extracts of living organisms), as the extracted cellular product from Staphylococcus aureus was used as a catalyst for the reduction of nickel nitrate salt (Ni(NO3)2) to Nickel Oxide nanoparticles, in addition to the therapeutic applications of nanoparticles that will be used against MDR-A. baumannii bacteria, after characterizing these NiO nanoparticles using UV-VIS spectroscopy, AFM (Atomic Force Microscopy), XRD (X-ray diffraction), FE-SEM (field emission scanning electron microscopy), FTIR (fourier transform infrared) and EDX (Energy- Dispersive X-ray spectroscopy) and this is to understand the properties of NiO NPs. The results revealed that Nickel Oxide nanoparticles with a nanosize of 63.81 nm were characterised by AFM microscopy and spherical shape under FE-SEM, the results also indicated the identification of MDR-A.baumannii isolates possessing high resistance In the following study and antibacterial activity test against MDR-A.baumannii was carried out against MDR-A.baumannii using different concentrations of Nickel Oxide nanoparticles (500 µg/ml, 1 mg/ml, 2 mg/ml and 4 mg/ml), the results of the in vitro evaluation of bacterial biosynthesised Nickel Oxide nanoparticles as antibacterial showed that the Maximum Inhibitory Concentration (MIC) was 4 mg/ml with an area diameter of 22 mm, while the Minimum Inhibitory Concentration (MIC) was 2 mg/ml with an area diameter of 18 mm, the biosynthesis of Nickel nanoparticles showed promising antibacterial activity. The eradication of biofilms using NIO NPs in multidrug-resistant bacteria MDR-A.baumannii at concentrations of 4 ml/gm and 8 ml/gm, respectively, against biofilm production, showed that nickel nanoparticles had a significant antibacterial and biofilm inhibitory effect, which could have applications as a treatment against multidrug resistant MDR-A.baumannii bacteria.